Distribution and Factors Affecting Investment in Yogyakarta Special Region - Khosiyatillah, Umi (Universitas Negeri Semarang, 2021)
This study aims to determine the distribution of investment for each PMA and PMDN in DIY in 2019, classify regions based on investment for PMA and PMDN, and determine the factors that affect investment PMA and PMDN in DIY. This study uses secondary data. The variables used in this research are PMA and PMDN investment, labor force, Human Development Index (IPM), Regional Minimum Wages (UMR), and Local Taxes. This study's population and sample were 5 districts/cities for the PMA and PMDN investment models. Descriptive analysis is using to determine the distribution of investment, Klassen typology to classify areas based on investment, and choose the factors that affect investment using the panel data method. The results showed that: (1) The distribution of PMA and PMDN investment in DIY was still not evenly distributed. (2) The regional classification based on investment shows that Kulonprogo, Bantul, and Gunungkidul districts lack foreign investment. Meanwhile, the districts of Sleman, Bantul, and Gunungkidul lack domestic investment. (3) Factors that influence PMA are UMR and IPM, and factor that influence PMDN are labor force. Tujuan dari penelitian ini adalah untuk mengetahui sebaran investasi untuk masing-masing investasi PMA dan PMDN di DIY tahun 2019, mengklasifikasikan daerah berdasarkan investasi untuk masing-masing investasi PMA dan PMDN, dan mengetahui faktor-faktor yang mempengaruhi investasi untuk masing-masing investasi PMA dan PMDN di DIY. Penelitian ini menggunakan data sekunder. Variabel yang digunakan dalam penelitian ini adalah Investasi PMA dan investasi PMDN, Angkatan kerja, Indeks Pembangunan Manusia (IPM), Upah Minimum Regional (UMR), dan Pajak Daerah. Populasi dan sampel dalam penelitian ini adalah 5 kabupaten/kota untuk model investasi PMA dan PMDN. Hasil penelitian menunjukkan bahwa: (1) Sebaran investasi PMA dan PMDN di DIY masih belum merata. (2) Klasifikasi daerah berdasarkan investasi menunjukkan Kabupaten Kulonprogo, Bantul, dan Gunungkidul kekurangan investasi PMA. Sedangkan Kabupaten Sleman, Bantul, dan Gunungkidul kekurangan investasi PMDN. (3) Faktor yang mempengaruhi investasi PMA yaitu UMR (Upah Minimum Regional) dan IPM (Indeks Pembangunan Manusia) dan faktor yang mempengaruhi investasi PMDN yaitu Angkatan kerja.